Carl Niekerk and Cori Crane, eds. Approaches to Kurban Said’s Ali and Nino: Love, Identity, and Intercultural Conflict. Camden House, 2017. - Ervin Malakaj (Studies in 20th & 21st Century Literature, 2018)
Review of Carl Niekerk and Cori Crane, ed. Approaches to Kurban Said’s Ali and Nino: Love, Identity, and Intercultural Conflict. Camden House, 2017. ix + 277 pp.
Keywords: Kurban Said; Ali and Nino